The influence of nutritional status, physical fitness, and self-perception on student learning outcomes: a conceptual review - Septa Saiman; Aldo Naza Putra; Alnedral Alnedral; Liza Liza (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Elementary physical education learning outcomes are often examined through isolated physiological or psychological variables, leading to fragmented theoretical explanations. This study aims to develop an integrated conceptual understanding of how nutritional status, physical fitness, and self-perception relate to learning outcomes in elementary physical education. A Conceptual Review was conducted using a narrative synthesis of national and international peer-reviewed literature published between 2018 and 2025. Relevant studies were analyzed to identify dominant conceptual patterns, theoretical positions, and relational mechanisms among the three constructs. The analysis indicates that nutritional status and physical fitness function as foundational physiological conditions, while self-perception operates as a central psychological mechanism mediating students’ engagement and learning participation. Unlike previous research that treats these factors independently, this study proposes a unified conceptual framework that explains their interrelationships. This framework contributes to advancing holistic perspectives in physical education theory and provides a theoretical foundation for future empirical research and integrative educational interventions.